Предмет:
МатематикаАвтор:
анонимРешение:
(х - у) + х(у - х) = (х - у) - х(x - y) = (х - у)(1 - х).
n(m - n)2 - (n - m)3 = n(m - n)2 + (m - n)3.
Вынесем общий множитель (m - n)2 за скобку:
(m - n)2(n + m - n) = m(m - n)2.
a(a - c)2 - c(a - c)(c - a) = a(a - c)2 + c(a - c)(a - c) = a(a - c)2 + c(a - c)2 = (a - c)2(a + c).
Ответ: 1. (х - у) + х(у - х) = (х - у)(1 - х); 2. n(m - n)2 - (n - m)3 = m(m - n)2; 3. a(a - c)2 - c(a - c)(c - a) = (a - c)2(a + c).
Автор:
martínbyrdДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть